The 4KEEPS study: identifying predictors of sustainment of multiple practices fiscally mandated in children's mental health services. (December 2015) - Lau, Anna; Brookman-Frazee, Lauren
Abstract Background Research to date has largely focused on predictors of adoption and initial implementation of evidence-based practices (EBPs), yet sustained implementation is crucial to deliver a return on investments in dissemination. Furthermore, most studies focus on single EBPs, limiting opportunities to study the fit between practice characteristics EBPs and implementation contexts. Methods/design This observational study will characterize implementation sustainment and identify organizational and therapist characteristics that predict sustainment of multiple practices being implemented within a fiscal mandate in the largest public mental health system in the USA. Specific aims are to (1) characterize sustainment outcomes (volume/penetration, EBP concordant care); (2) use mixed methods to characterize inner context (agency- and therapist-level) factors and early implementation conditions; and (3) identify inner context factors and early implementation conditions that predict sustainment outcomes. This study will undertake original data collection and analysis of existing data sources to achieve its aims. Archived reports and documents will be used to characterize early implementation conditions in 102 agencies. Administrative claims data will be used to characterize volume and penetration outcomes over 8 years. Therapist and program manager surveys will be administered to characterize sustained EBP concordant care and inner context determinants of sustainment. An in-depth study in a subset of agencies will yield interview data and recordings of treatment sessions for validation of the EBP concordant care scale. Discussion This project will yield new understanding of whether and how multiple EBPs can be sustained in public mental health systems undergoing a policy-driven community implementation effort. We will produce generalizable models for characterizing sustainment, including feasible and flexible measurement of practice across multiple EBPs. The findings will inform the development of implementation interventions to promote sustained delivery of EBPs to maximize their public health impact.